Internet Freedom As Human Right? - Rina Arum Prastyanti; Eiad Yafi; S.Andi Sutrasno (Proceeding of International Conference on Science, Health, And Technology, 2019)
In the international world, the protection of human rights and the internet has become one of the important discussions at the United Nations. In 2012, the United Nations issued a Resolution on the Promotion, Protection and Enjoyment of Human Rights on the internet, one of which acknowledged that expressions delivered online received the same protection in offline expression activities. But in Indonesia the government has blocked internet and data services due to demonstrations in several regions such as Jayapura, Manokwari, Sorong, and Fakfak. Blocking actions on a number of platforms or internet sites, has drawn a number of polemics in the public. These actions are often judged disproportionately. This research is in accordance with the grouping of the concepts of the fifth law, namely the law is a manifestation of the symbolic meanings of social actors as seen in their interactions. This type of research is sociological (non-doctrinal) legal research. Research Approach is a sociolegal study which is a study of law using the approach of law and social sciences. Empirical social research or socio legal research only places law as a social phenomenon. Therefore, in this study social problems have always been linked. Method of Collecting Data that used in this research is in-depth interview data collection techniques and literature study. Validity Data in This research uses data triangulation and information from one party is verified by obtaining information from other sources. For example from second parties, third parties and so on using different methods. The data analysis technique used in this study is qualitative data analysis. Internet content governance policies, in addition to providing clear classification restrictions regarding content, should also contain the following elements: first, control of internet information (control to content) which is closely related to the role of key actors in managing the internet as public goods (netizens) including oversight mechanisms; second, access to services (access to internet service) that provides a set of rules on how the position of the role of internet intermediaries (rule of internet intermediaries) in managing internet information; third, protection of vulnerable groups (children, women,); and fourth, the remedy mechanism (remedy mechanism) if certain actions have an undue impact in relation to the enjoyment of access to knowledge. In this context, governance policies in Indonesia still show a number of shortcomings.